Evaluation of the catalytic effect and migration behavior of potassium in the molten slag during the char/molten slag interfacial gasification. (1st January 2022) - Bao, Xiaodan; Shen, Zhongjie; Zhang, Haigang; Liang, Qinfeng; Liu, Haifeng
Highlights: Adding K to molten slag has catalytic effect on char-slag interfacial gasification. K in molten slag was found to migrate to char-slag interface during gasification. K accumulation on char/slag interface increased with increasing carbon conversion. Mechanism of K migration related to catalytic effect was proposed in this study. Abstract: The reaction of coal char particles deposited on the molten slag surface in the entrained flow gasifier was of importance to the carbon conversion and slag discharge. In this study, the catalytic effect and migration behavior of the alkali metal (K) in molten slag during the gasification reaction of char particles on the molten slag surface were investigated and evaluated by using visualization and surface analytical techniques. The results showed the ionic K in the molten slag was not deactivated and accelerated the char gasification rate and carbon conversion of char particle on the molten slag surface as a catalytic effect. The complete conversion time of char particles on the molten slag with the addition of K was reduced by about 37%–67%, compared to the time of the char gasification without molten slag or the gasification on the slag with no addition of K. The carbon conversion of char particles was increased obviously with increasing the addition of K in the molten slag. From the analyses of scanning electron microscope (SEM) and energy dispersive spectrometry (EDS), the ionic K was found to gradually migrate and accumulate to the interface between the coal char particle and molten slag during the gasification process. The migrating and accumulating amount of K to the interface increased with the increases of both carbon conversion of the char particle and K addition of the slag. With a comparative experiment of the char combustion on the slag surface, a low temperature zone below the char particle during the gasification was key to cause a migration behavior of K with other elements (e.g. Si and Al) and further acted as a catalytic effect on the gasification reaction. Finally, a mechanism of the catalytic effect and migration behavior of ionic K in the slag during the char/molten slag interfacial gasification process was uncovered in this study.